Social normativity, housing, and urbanisation in an Indian city. Issue 6 (17th August 2016) - Kumar, Mukul
ABSTRACT: A significant part of urbanisation in India is happening through unregulated or partly regulated trajectories that are either informal or semi-formal in nature, and regulatory authorities have come to terms with them on a piecemeal basis over a period of time. This article contends that what is considered unplanned by regulatory agencies is actually planned by people and facilitated by the normativity surrounding both formal and informal institutions of urbanisation in society. The study looks at the processes through which such a housing settlement comes into being and negotiates legitimacy, authorisation, as well as basic civic services.